(untitled) (Jurnal Adabiya, 2025)
The development of social media, especially Instagram, opens up great opportunities for mosques to convey information widely, quickly, and transparently to the public. However, there are still many mosques that have not utilized social media optimally as a media for information literacy, including old mosques that are in the construction stage in the city of Banda Aceh. This condition requires strengthening the capacity of human resources, especially mosque youth, in the management of mosque digital communication. This research-based service-based research aims to train and empower mosque teenagers in managing Instagram accounts as an information literacy media and a means of public information disclosure to the public. The method used is Community Based Research (CBR) involving various mosque stakeholders, namely mosque youth, mosque imams, development committees, mosque prosperity committees, and community leaders. This approach emphasizes the active participation of the community in all stages of service, from planning, implementation, to evaluation. The results of the service show that mosque teenagers have been able to use Instagram as an information literacy medium, including the publication of routine activity schedules, teachers’ advice, daily mosque information, and periodic financial reports. The use of Instagram not only improves the digital communication skills of mosque teenagers, but also strengthens information disclosure and public trust in mosque management. ABSTRAK Perkembangan media sosial, khususnya Instagram, membuka peluang besar bagi masjid untuk menyampaikan informasi secara luas, cepat, dan transparan kepada masyarakat. Namun, masih banyak masjid yang belum memanfaatkan media sosial secara optimal sebagai media literasi informasi, termasuk masjid-masjid tua yang berada dalam tahap pembangunan di Kota Banda Aceh. Kondisi ini menuntut adanya penguatan kapasitas sumber daya manusia, terutama remaja masjid, dalam pengelolaan komunikasi digital masjid. Penelitian berbasis pengabdian berbasis riset ini bertujuan untuk melatih dan memberdayakan remaja masjid dalam mengelola akun Instagram sebagai media literasi informasi dan sarana keterbukaan informasi publik kepada masyarakat. Metode yang digunakan adalah Community Based Research (CBR) dengan melibatkan berbagai pemangku kepentingan masjid, yaitu remaja masjid, imam masjid, panitia pembangunan, panitia kemakmuran masjid, serta tokoh masyarakat. Pendekatan ini menekankan partisipasi aktif komunitas dalam seluruh tahapan pengabdian, mulai dari perencanaan, pelaksanaan, hingga evaluasi. Hasil pengabdian menunjukkan bahwa remaja masjid telah mampu memanfaatkan Instagram sebagai media literasi informasi, meliputi publikasi jadwal kegiatan rutin, petuah guru, informasi harian masjid, hingga laporan keuangan secara berkala. Pemanfaatan Instagram tidak hanya meningkatkan keterampilan komunikasi digital remaja masjid, tetapi juga memperkuat keterbukaan informasi dan kepercayaan masyarakat terhadap pengelolaan masjid